(untitled) (Politeja, 2022)
EASTERN PARTNERSHIP AS A PLACE OF CIVIL SOCIETY FORMATION – A PLAN FOR THE NEXT EU ENLARGEMENT? The article is an attempt to look at the EU enlargement policy from the angle of the Eastern Partnership as a place of civil society formation. The aim is to present the main motives of the next EU enlargement to the east. The research was based on a qualitative methodology with the use of institutional, legal and comparative analysis. The research material covered original acts and press releases of EU institutions, key scientific studies and internet portals devoted to the issue. The research shows the shaping of civil society in the EaP states creating a new perspective for the program and speaks in favor of EU enlargement in this direction.